2021
DOI: 10.1177/10547738211045850
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Progressive Relaxation Exercises on Vital Signs and Fatigue in Liver Transplant Patients: A Randomized Controlled Trial

Abstract: This randomized controlled study was conducted to evaluate the effects of progressive relaxation exercises on vital signs and fatigue level. Ninety patients with liver transplantation (experimental group = 45, control group = 45) were included in the study. The patients in the experimental group performed progressive relaxation exercises for 25 to 30 minutes every day for 4 weeks. Before the progressive relaxation exercises, the vital signs and fatigue level of the patients were recorded. Vital signs were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…19,44,47,48 Studies for participants with hemodialysis, 49 head and neck cancer, 21 and gynecological cancer, 31 participants receiving chemotherapy for the first time, 45 and participants with breast cancer 30,50 have shown that PMR has positive and curative effects on fatigue. Moreover, studies that have been conducted with participants with fibromyalgia, 20 participants in the post-liver transplant period, 51 participants with diabetes, 52 participants with rheumatoid arthritis, 53 and multiple sclerosis 54 have shown that PMR has positive and curative effects on fatigue. In studies with different participant groups, positive effects of PMR on fatigue were observed, similar to the results of the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,44,47,48 Studies for participants with hemodialysis, 49 head and neck cancer, 21 and gynecological cancer, 31 participants receiving chemotherapy for the first time, 45 and participants with breast cancer 30,50 have shown that PMR has positive and curative effects on fatigue. Moreover, studies that have been conducted with participants with fibromyalgia, 20 participants in the post-liver transplant period, 51 participants with diabetes, 52 participants with rheumatoid arthritis, 53 and multiple sclerosis 54 have shown that PMR has positive and curative effects on fatigue. In studies with different participant groups, positive effects of PMR on fatigue were observed, similar to the results of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies that have been conducted with participants with fibromyalgia, 20 participants in the post-liver transplant period, 51 participants with diabetes, 52 participants with rheumatoid arthritis, 53 and multiple sclerosis 54 have shown that PMR has positive and curative effects on fatigue. In studies with different participant groups, positive effects of PMR on fatigue were observed, similar to the results of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Kömürkara ve Cengiz (36), progresif gevşeme egzersizlerinin yaşamsal belirtiler ve yorgunluk düzeyi üzerindeki etkilerini değerlendirmek için planladıkları çalışmaya karaciğer nakli yapılan 90 hasta (deney grubu=45, kontrol grubu=45) dahil edilmiştir. Deney grubundaki hastalar 4 hafta boyunca her gür 25-30 dakika PGE uygulamıştır.…”
Section: Progresif Gevşeme Egzersizlerinin Yorgunluk üZerine Etkileriunclassified
“…The progressive muscle relaxation (PMR) technique is learning to relax some groups of muscles while paying attention to the feelings connected with both the tense and relaxed states. [6] It has been proposed that PMR lowers the heart rate, [7] Systolic, and diastolic BP, [8] respiratory rate. [7] and anxiety by reducing neural reflex function, which decreases musculoskeletal neural input and output activity, thus reducing the stress level in hypertensive people.…”
Section: Introductionmentioning
confidence: 99%
“…[6] It has been proposed that PMR lowers the heart rate, [7] Systolic, and diastolic BP, [8] respiratory rate. [7] and anxiety by reducing neural reflex function, which decreases musculoskeletal neural input and output activity, thus reducing the stress level in hypertensive people. PMR has been used in numerous empirical studies with positive physiological effects in many populations.…”
Section: Introductionmentioning
confidence: 99%